2020
DOI: 10.3390/su12125116
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development of the Mortgage Market in Azerbaijan: Commercial Risks of Housing Construction, Social Vision, and State Influence

Abstract: The purpose of this study is to formulate a model for sustainable development of the mortgage market in Azerbaijan, taking into account commercial risks of housing construction, the risks of the construction industry, social visions of mortgages, state pressure, and support. The following five key research stages can be distinguished. Namely, identification of commercial risks of housing construction based on a survey; evaluation of the effectiveness of risk diversification strategy; determination of the socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Russia demonstrated external stability against the backdrop of COVID-19-induced economic challenges, while Azerbaijan revealed the non-competitive quality of the current market model. Baik et al [64] and Ganbarov et al [65] found that the country's market environment influences the profitability of the facility and its strategic behavior. The researchers identified culture, quality of accounting standards, and political and legal environment as influential factors.…”
Section: Discussionmentioning
confidence: 99%
“…Russia demonstrated external stability against the backdrop of COVID-19-induced economic challenges, while Azerbaijan revealed the non-competitive quality of the current market model. Baik et al [64] and Ganbarov et al [65] found that the country's market environment influences the profitability of the facility and its strategic behavior. The researchers identified culture, quality of accounting standards, and political and legal environment as influential factors.…”
Section: Discussionmentioning
confidence: 99%
“…The need for active participation of political authorities in the regulation of the housing and communal services market is shown in researches on the development of Mortgage banking in Slovakia over a 20-year period (Horvatova 2020) and the Mortgage market in Azerbaijan (Ganbarov et al 2020).…”
mentioning
confidence: 99%